Schooling and Income Distribution - Marin, Alan; Psacharopoulos, George (The Review of Economics and Statistics, 1976)
ONE question that arises following recent I attempts to introduce economic theory in explaining income distribution is to what extent schooling can be used as a policy instrument to promote equality in our society. Although the link between the size of individual earnings and education has been rather well established, the change in the distribution of income among individuals resulting from a change in the level of schooling is not yet settled. In this paper we elaborate on the relationship between schooling and income distribution based on human capital theory. In order to answer the question we need an expression relating a measure of income distribution to a measure of education. It would be convenient in this respect to start from the work of what we will call the Becker-MincerChiswick (B-M-C) group,1 as perhaps the best known of those providing such an expression. In their work the level of earnings (Y) of an individual with S years of schooling is determined by an earnings generating function of the form